2018
DOI: 10.21053/ceo.2018.00178
|View full text |Cite
|
Sign up to set email alerts
|

Body Surface Area Is Not a Reliable Predictor of Tracheal Tube Size in Children

Abstract: ObjectivesThe age-based Cole formula has been employed for the estimation of endotracheal tube (ETT) size due to its ease of use, but may not appropriately consider growth rates among children. Child growth is assessed by calculating the body surface area (BSA). The association between the outer diameter of an appropriate uncuffed-endotrachealtube (ETT-OD) and the BSA values of patients at 24–96 months of age was our primary outcome.MethodsCole formula, BSA, age, height, weight and ultrasound measurement of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
(36 reference statements)
0
6
0
1
Order By: Relevance
“…We systematically studied and evaluated the use of US for the assessment of ETT size in the pediatric age group Table 3 . [ 4 5 6 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ] We wanted to examine whether the US measurements give us a reasonable enough idea of the size of the ETT to be inserted, whether there is any co-relation of US with the traditional formulas. Additional information was also gathered regarding the impact of the US learning curve, ease of insertion of the ETT, depth of insertion of the ETT, utility of the US to detect correct placement, any effect of the US on the ETT exchange rates, whether the real-time US reduced the need for repeated laryngoscopy and thus avoided airway trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We systematically studied and evaluated the use of US for the assessment of ETT size in the pediatric age group Table 3 . [ 4 5 6 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ] We wanted to examine whether the US measurements give us a reasonable enough idea of the size of the ETT to be inserted, whether there is any co-relation of US with the traditional formulas. Additional information was also gathered regarding the impact of the US learning curve, ease of insertion of the ETT, depth of insertion of the ETT, utility of the US to detect correct placement, any effect of the US on the ETT exchange rates, whether the real-time US reduced the need for repeated laryngoscopy and thus avoided airway trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The subglottic diameter is calculated using a high-resolution US computer linear probe mounted on the midline of the anterior neck with the head extended and neck flexed during mask ventilation. The subglottic tracheal diameter measured was used to pick an endotracheal tube of similar outer diameter in the studies done by Shibasaki M et al ,[ 4 ] Uzumcugil et al ,[ 11 ] Bhardwaj N et al ,[ 14 ] Gollu G et al ,[ 19 ] Kumar A et al . [ 33 ] The endotracheal tube with an outer diameter often less than the measured tracheal diameter was chosen to avoid damage to the airways.…”
Section: Discussionmentioning
confidence: 99%
“…Their increase correlated with age; different races cause the population to present phenotypic differences worldwide. The graphs of weight percentiles for the period and height-for-age are used to monitor growth; children in the <5 % weight and height-for-age range (with pathologically short stature) may have a smaller tracheal diameter relative to their age; this was stated by Daugherty et al [5] when determining that the predictions based on height were not accurate, the same as defined in another retrospective study in which 5175 records of patients with short stature were analyzed. It was concluded that the prediction of tube size based on height is as short stature as the estimate based on age, both in patients with pathological and nonpathological short length [14], thus showing that formulas such as Cole, Khine, and Motoyama can be misleading in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging methods, such as computed tomography and magnetic resonance imaging, are impractical apart from expensive. On the other hand, US is a method that allows easy, fast and precise visualization of the supraglottic, glottic and subglottic regions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Pediatrik hasta grubunda uygun endotrakeal tüp (ETT) çapının belirlenmesinin nasıl yapılacağı halen tartışmalıdır. Bu durum; anatomik, yapısal ve ırksal farklılıklar nedeniyle çeşitli formüller geliştirilerek çözülmeye çalışılmaktadır (3)(4)(5) . Bu amaçla günümüzde seçilecek olan ETT'nin çapını yaş, boy ve kiloya göre hesaplamaya olanak sağlayan Cole formülü gibi değişik formüller kullanılmaktadır.…”
Section: Introductionunclassified